'She Did but Take up Old Stories': Generic Fluidity and Women's Life Writing of the Early Eighteenth Century. Issue 2 (1st September 2014) - Joule, Victoria
Abstract : In this article I demonstrate the significance of a flexible approach to examining the autobiographical in early eighteenth-century women's writing. Using 'old stories', existing and developing narrative and literary forms, women's autobiographical writing can be discovered in places other than the more recognizable forms such as diaries and memoirs. Jane Barker and Delarivier Manley's works are important examples of the dynamic and creative use of cross-genre autobiographical writing. The integration of themselves in their fictional and poetic works demonstrates the potential of generic fluidity for innovative ways to express and explore the self in textual forms.